The Returns to School Quality: College Choice and Earnings - Strayer, Wayne (Journal of Labor Economics, 2002)
This article extends the research on school quality by focusing on the structural effects of high school quality on earnings. I specify a model of college choice and earnings determination that captures two separate effects of school quality on earnings. First, school quality affects a high school student's choice of college. College choice, in turn, affects the individual's postschool earnings. Second, the additional skills accumulated via a higher quality high school directly influence wages. The results suggest that high school quality influences earnings by affecting college choice behavior, while the direct effect of school quality on earnings is less evident.